Pengaruh Net Profit Margin (NPM) Dan Total Asset Turnover (TATO) Terhadap Return On Asset (ROA) Pada Perusahaan Sub Sektor Farmasi Yang Terdaftar Di Bursa Efek Indonesia Periode 2020-2024 - Wildan Fathil Padil; Dava Indira Dandy; Alfiana Alfiana (Indonesia Economic Journal, 2026)
This study aims to analyze the effect of Net Profit Margin (NPM) and Total Asset Turnover (TATO) on Return on Assets (ROA) in pharmaceutical companies listed on the Indonesia Stock Exchange for the 2020–2024 period. This study uses quantitative methods with secondary data in the form of annual financial reports. The research sample consisted of six companies with a total of 30 observations, analyzed using panel data regression. Based on the results of the model selection test, the best model used was the Random Effects Model (REM). The results show that partially, NPM has a positive and significant effect on ROA, while TATO has no significant effect on ROA. However, simultaneously, NPM and TATO significantly influence ROA. The Adjusted R-squared value of 0.770689 indicates that the independent variables explain 77.07% of the variation in ROA. This study implies that increasing profitability in pharmaceutical companies is more influenced by the ability to generate net income than by asset turnover efficiency.